KETERBUKAAN TERHADAP PENGALAMAN, ORGANIZATIONAL CITIZENSHIP BEHAVIOR DAN BUDAYA ORGANISASI BERORIENTASI KARYAWAN SEBAGAI PREDIKTOR KINERJA KARYAWAN - , Pratista Arya Satwika, Drs. Fathul Himam, MPsi., MA., Ph.D., Psi ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Globalization era demands high organizationâs performance to survive. There are some human resource problems in Indonesia that indirectly influence individual performance in the organization. This research is aimed to determine openness to experience, organizational citizenship behavior and employee-oriented organizational culture as employee performance predictor. Hypothesis that is proposed in this research is openness to experience, organizational citizenship behavior and employee-oriented organizational culture as employee performance predictor. This research is a field study that uses quantitative methodology, by using questionnaire as data collecting tool. Questionnaire used is questionnaire about openness to experience (McCrae & Costa, 2003), organizational citizenship behavior (Organ, Podsakoff & MacKenzie, 2006), employee-oriented organizational culture (Hofstede, Hofstede & Minkov, 2010), and employee performance (Bernardin & Russel, 1998